A Collective Review of the Research on Training the Oldest-Old - Capanema B.D.S.V.* (2022)
© 2022 Lippincott Williams and Wilkins. All rights reserved.To synthesize the scientific evidence on physical exercise protocols for the oldest-old we searched PubMed, Scopus, Web of Science, CINAHL, Medline, and gray literature up to January 2021. Eligibility criteria included investigation of the oldest-old population (≥80 years); use of intervention protocols with appropriate and effective variables for a physical exercise program (type, intensity, frequency, and duration); reporting positive effects of the interventions on physical fitness, execution of activities of daily living, and quality of life of the oldest-old; an experimental and/or quasiexperimental (randomized or nonrandomized) study design. Twenty studies were included. Physical exercise protocols for the oldest-old should include strength, power, aerobic endurance, flexibility, balance, and joint mobility exercises. These exercises are effective in attenuating or minimizing the declines that occur during aging, improving factors such as gait, fall rate, and functional capacity.